PENDIDIKAN KARAKTER DALAM AL-QURAN SURAT AL-HUJURAT - Zulkarnain S (Universitas Islam Negeri Fatmawati Sukarno, 2016)
Alquran al-Hujurat contain values which can be a reference to a character in a character education in Indonesia, which is facing a moral crisis. The type is library research with critical analytical method and analytic interpretation.The Issues raised are: how al - Hujurat reveal character education?, what values of character education are contained in it? and what are the implications of character education in Surat al - Hujurat in the world of education? The results showed that the character education contained in al-Hujurat included manners to God, to the Prophet Muhammad and to his fellow man of him. There are values of commendable character and values of despicable character in it. Implications of character education in al-Hujurat to the world of education is that educators (teachers) and learners (students) must adhere to the ethics code of teachers and pupils.